Relationship of brain edema after deep brain stimulation surgery with motor and cognitive function. Issue 2 (February 2022) - Nishiguchi, Yamato; Matsuura, Keita; Hirata, Yoshinori; Mizutani, Akane; Katoh, Natsuko; Ishikawa, Hidehiro; Miyashita, Koichi; Utsunomiya, Takaya; Kajikawa, Hiroyuki; Nishikawa, Hirofumi; Araki, Tomohiro; Shindo, Akihiro; et al.
Abstract: Background: Some patients with Parkinson's disease (PD) develop peri-lead brain edema after deep brain stimulation (DBS) surgery. The influence of edema on neurological function is not well characterized. We investigated the relationship of brain edema after DBS surgery with motor and cognitive function. Methods: Thirteen patients with PD (6 males and 7 females; mean age: 61.2 years) who underwent bilateral subthalamic nucleus (STN) DBS surgery were included. All patients underwent magnetic resonance imaging (MRI) examination on day 6 post-DBS surgery. The volume of edema was measured either in the frontal white matter or STN on fluid attenuated inversion recovery (FLAIR) images. We examined the relationship between these volumes and changes in cognitive and motor function. Results: Patients were divided into those with frontal subcortical edema (FE) ≥3, 000 mm 3 (FE + group; n = 7) and <3, 000 mm 3 (FE–group; n = 6). In the FE + group, the postoperative Mini-Mental State Examination score worsened by 2.4 points after one week compared with that immediately before surgery, while that in the FE-group worsened only by 0.2 points (p = 0.038). On comparing patients with peri-STN edema (SE) ≥1, 000 mm 3 (SE + group; n = 3) and those with SE < 1, 000 mm 3 (SE-group; n = 10) showed that frequency of DBS tuning in the early postoperative period of the SE + group was lesser than that in the SE-group. Conclusions: Development of FE after DBS surgery was related to transient cognitive decline. On the other hand, SE seemed associated with altered motor function and reduces the requirement for tuning in the initial period after DBS implantation. Highlights: Peri-lead brain edema was sometimes developed after deep brain stimulation surgery. Development of frontal subcortical edema was related to transient cognitive decline. Peri sub-thalamic nucleus edema seemed associated with altered motor function. Abstract : Parkinson's disease; Deep brain stimulation; Brain oedema; Magnetic resonance imaging; Micro lesion effect; Subthalamic nucleus.